Tinjauan Atraksi Ekowisata Di Kawasan Ecovillage Tangkahan, Kabupaten Langkat, Provinsi Sumatera Utara - Sabam Syahputra Manurung (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
Through an approach that focuses on environmental conservation, education, and community involvement, ecotourism opens new avenues to create a balanced relationship between humans and nature. Tangkahan Ecovillage is located in the Gunung Leuser National Park (TNGL) area, Langkat Regency which has started ecotourism activities since 2004. In 19 years of its journey, it is interesting to discuss the description of ecotourism attractions in this region. This research was developed through a qualitative descriptive method. The process of collecting data through interviews, observations and document studies. The results of the research are presented in the form of narratives that describe the situation at the research site, direct quotes from participants, and supported by images or illustrations to clarify the findings.This research results in ecotourism has played an important role in becoming a bulwark of defense from increasingly massive forest destruction activities. Tourist attractions in the form of elephant conservation, river and forest area exploration, camping ground, and natural attractions at the location have proven to be in demand by local and foreign tourists. Local communities who are members of the Community Tour Operator (CTO) manage tourism services well with the principle of profit sharing. Furthermore, the tourist community utilizes this activity as an economic source and as a medium of education for the wider community on the importance of preserving nature so that Tangkahan ecotourism can be enjoyed by everyone in the long term..